Cranial Autonomic Symptoms among Migraine Diagnosed Patients: Prevalence and Clinical Implications - Manoj Dhungana; Sanjeev Shah; Rajesh Shrestha; Arpana Pokhrel (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Cranial autonomic symptoms (CAS) are increasingly identified in migraine patients, making diagnosis more challenging due to similarities with Trigeminal Autonomic Cephalagias (TACs). This study is conducted to determine the prevalence of CAS in Nepalese migraine cohort and highlight diagnostic in improving diagnostic accuracy and guiding individualized treatment in resource limited setting. MATERIAL AND METHODS This cross-sectional study involved 150 migraine patients at a Medical College Headache clinic, Department of Psychiatry in Nepal. Psychiatrists applied ICHD-3 beta criteria for diagnosis and assessed the presence of CAS. Data were collected using a pretested structured interview questionnaire and analyzed with SPSS version 16, using both descriptive and inferential statistics. Ethical approval was obtained from the Institutional review Committee (IRC-DMCRI/047/2022) of Devdaha Medical College, and written informed consent was secured. Strict confidentiality of participants’ information was maintained throughout the study. RESULTS At least one CAS was reported by 73.3% of patients. The most common symptoms were eyelid edema (54.5%), conjunctival injection (49.1%), lacrimation (47.3%), and aural fullness (45.5%). CAS occurred more often in males (86.7% vs. 70% in females) and was most frequent in the 20-30 year of age group (85.0%). CONCLUSION CAS is common in migraine and may mimic TACs or other secondary headaches. Routine screening can improve diagnostic accuracy and guide individualized treatment plans.